2020
DOI: 10.1186/s12890-020-1073-6
|View full text |Cite
|
Sign up to set email alerts
|

Does a pulmonary rehabilitation based ERAS program (PREP) affect pulmonary complication incidence, pulmonary function and quality of life after lung cancer surgery? Study protocol for a multicenter randomized controlled trial

Abstract: Background: Lung cancer surgery is associated with a high incidence of postoperative pulmonary complications (PPCs). Preliminary evidence suggests that ERAS processes can reduce overall incidence of PPCs as short-and longterm recovery improved by supporting units to adopt evidence-based care. However, the evidence is inconclusive due to insufficient high-level studies in this research field. No well-designed, adequately powered, randomized controlled trials (RCTs) have investigated the effects of pulmonary reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Research by Huang et al (36) showed that compared with traditional perioperative care, ERAS reduced postoperative pain and shortened chest tube indwelling time. Furthermore, previous studies have found a substantial difference in quality of life between the ERAS program and standard care, which indicates that ERAS is beneficial (71,72). There is also evidence that the LOS of patients treated with the ERAS program is shorter (73).…”
Section: Discussionmentioning
confidence: 95%
“…Research by Huang et al (36) showed that compared with traditional perioperative care, ERAS reduced postoperative pain and shortened chest tube indwelling time. Furthermore, previous studies have found a substantial difference in quality of life between the ERAS program and standard care, which indicates that ERAS is beneficial (71,72). There is also evidence that the LOS of patients treated with the ERAS program is shorter (73).…”
Section: Discussionmentioning
confidence: 95%
“…It was conducted in accordance with the Declaration of Helsinki and was approved by the Institutional Review Board of the coordinating centre (2019-SR-360). The original protocol was published in 202019; any deviations are documented in online supplemental material 1.…”
Section: Methodsmentioning
confidence: 99%
“…Patients scheduled for lung cancer surgery were screened for eligibility. Consolidated criteria for patient enrolment are summarised in table 1 19. Eligible patients were then invited to participate in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Although thoracoscopic lobectomy is more conducive to patient recovery, the probability of various complications after thoracoscopic surgery remains high at 15.8-31.7%, mainly involving pulmonary air and pleural effusion such that, when taking into account the different stages of cancer, 25-70% of patients eventually relapse (11)(12)(13). The complication rate for thoracoscopic lobectomy due to sputum retention and weakened respiratory muscle strength is as high as 19-59%, which seriously affects patient recovery (14).…”
Section: Introductionmentioning
confidence: 99%